Publications Received (Academy of Management Review, 1989)
The article presents a list of business publications received by the journal. They include “The Management Control Function,” by Robert N. Anthony, “The Long Interview,” by Grant McCracken, and “The Insider's Guide to the Top Ten Business Schools,” by Tom Fischgrund.